Involvement of the annexin A1-Fpr anti-inflammatory system in the ocular allergy - Marmorato, Mariana Prado; Gimenes, Alexandre Dantas; Andrade, Frans Eberth Costa; Oliani, Sonia Maria [UNESP]; Gil, Cristiane Damas (Elsevier, 2019)
Annexin A1 (ANXA1)-formyl peptide receptor (Fpr) system is potent effective mediators in the control of the inflammatory response. In this study, we evaluate the potential involvement of the Fpr family in the protective effect of the mimetic peptide of ANXA1 (ANXA12–26) using an experimental allergic conjunctivitis (AC) model in mice. Ovalbumin (OVA)/Alum-immunized wild-type (WT) and ANXA1-null (ANXA1-/-) Balb/c mice (days 0 and 7) were challenged by eye drops containing OVA on days 14–16, and two groups received ANXA12–26 alone or with Fpr antagonist Boc2 intraperitoneally during challenged days. As expected, plasma IgE anti-OVA levels increased significantly in the OVA-immunized WT and ANXA1-/- mice, supporting the efficacy of AC model. AC increased Fpr1 and Fpr2 levels in the conjunctiva and the lack of endogenous ANXA1 exacerbated Fpr2 expression only. In contrast, administering ANXA12–26 in the WT mice diminished Fpr2 levels in the conjunctiva, and the effect was reverted by Boc2. Ultrastructural analysis showed the co-localization of Fpr2 and ANXA1 in the plasma membrane of mast cells (MCs), eosinophils and neutrophils, supporting this system as being operative in the AC. Boc2 abrogated the ANXA12–26 effect by increasing the MC degranulation and the eosinophil influx in the conjunctiva, and these findings were supported by peroxidase eosinophil, eotaxin and MC protease levels. Additionally, the ANXA12–26-Fpr system in the AC was associated with the activation of ERK and JNK. Collectively, the data provided in vivo supports the anti-allergic effects of the ANXA1-Fpr system and may serve as a therapeutic target in this ocular disorder.
Keywords: Conjunctivitis; Eosinophils; Fpr2; Lipocortin 1; MAPK; Mast cells